Commemorating the Ross Sea Party: Antarctic heritage and international relations. Issue 1 (2nd January 2020) - Lintott, Bryan John
ABSTRACT: In 1917, Sir Ernest Shackleton's Imperial Trans-Antarctic Expedition (ITAE. 1914–17) drew to a close when he attached a copper tube enclosing an epitaph to commemorate the three members of the Ross Sea Party who had perished to a memorial cross on Wind Vane Hill, Ross Island, Antarctica. Shackleton's act and subsequent-related acts of commemoration, concluding in 2017, are analysed in the contexts of Antarctic heritage and international relations, with interrelationships. The research, on which this is based, identified relevant actors with their ideal values and utility values, intentions and actions. Structured analytical techniques, from intelligence studies, were applied. The paper is based on theory and methodology from Heritage Studies and International Relations. Abbreviations: ADM: Admiralty; [NZ]AHT: [New Zealand] Antarctic Heritage Trust; ANZW: Archives New Zealand, Wellington; ATCM: Antarctic Treaty Consultative Meeting; ATS: Antarctic Treaty System; CM: QA: Canterbury Museum: Quartermain Archive; CRO: Commonwealth Relations Office; DO: Dominion Office; DSIR: Department of Scientific and Industrial Research; FCO: Foreign and Commonwealth Office; HSM: Historic Sites and Monuments; ICOMOS: International Council on Monuments and Sites; ITAE: Imperial Trans-Antarctic Expedition; MFAT: Ministry of Foreign Affairs and Trade; NAA: National Archives of Australia; NMM: National Maritime Museum; RN: Royal Navy; RNR: Royal Navy Reserve; SPRI: Scott Polar Research Institute, University of Cambridge; UKAHT: United Kingdom Antarctic Heritage Trust; UKNA: United Kingdom, National Archives; USN: United States Navy